2020
DOI: 10.2147/ceor.s256671
|View full text |Cite
|
Sign up to set email alerts
|

<p>Malnutrition Prevalence and Burden on Healthcare Resource Use Among Spanish Community-Living Older Adults: Results of a Longitudinal Analysis</p>

Abstract: Purpose Little is known about the economic burden that malnutrition or its risk imposes on community-dwelling older adults. Using cross-sectional and longitudinal analyses, we assessed the impact of malnutrition risk on healthcare utilization and costs in a cohort of older adults living in Spanish community. Patients and Methods Data from 1660 older (range 66–98 years), community-living adults participating in the Toledo Study on Healthy Ageing, waves 2 (year 2011–2013)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 36 publications
2
15
1
Order By: Relevance
“…First, the constitution of our population has potentially brought a selection bias, as they are recruited volunteers. Furthermore, the malnutrition prevalence of 23.4% in our cohort appeared to be higher than the prevalence of 10.7% and 14% found in other studies using the GLIM criteria in community-dwelling older adults [60,61]. Consequently, our results could be limited in their external validity.…”
Section: Strengths and Limitationscontrasting
confidence: 89%
“…First, the constitution of our population has potentially brought a selection bias, as they are recruited volunteers. Furthermore, the malnutrition prevalence of 23.4% in our cohort appeared to be higher than the prevalence of 10.7% and 14% found in other studies using the GLIM criteria in community-dwelling older adults [60,61]. Consequently, our results could be limited in their external validity.…”
Section: Strengths and Limitationscontrasting
confidence: 89%
“…Within healthcare system outcomes, mortality was reported most frequently (n ¼ 33; 27%) [16,22,23,25,26,28e31, 34,37e42,44,45,53,55,57,60,61,65,67,68,73e75,80,83,85,89]. Other outcomes were hospitalization/readmissions/costs (n ¼ 11; 9%) [27,29,34,38,44,62,67,69,83,85,91], hospital and/or intensive care unit LOS (n ¼ 10; 8%) [27,34,44,53,65,67,77,83,91], complications (n ¼ 7; 6%) [53e55, 68,72,85], critical care admission (n ¼ 2; 2%) [42,67], and institutionalization (n ¼ 2; 2%) [16,29]. Patient outcomes included sarcopenia (n ¼ 6; 5%) [17,18,24,35,38,93], physical function (n ¼ 5; 4%) [38,57,75,80,93], quality of life (n ¼ 5; 4%) [56,59,64,74,75], falls/fractures (n ¼ 3; 2%) [29,38], frailty (n ¼ 2; 2%)…”
Section: Discussionmentioning
confidence: 99%
“…The global number of older adults with malnutrition is constantly increasing. The main causes of this phenomenon are demographic changes, the increasing proportion of elderly subjects in society, and the higher risk of poor nutritional status in elderly people compared to younger subjects [ 1 , 2 , 3 ]. The most common reason for malnutrition is an insufficient intake of calories (concerning requirements) [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Older people are at particular risk of malnutrition due to age-related physiologic changes, multimorbidity, psychological and socio-economic problems [ 9 , 10 , 11 ]. Malnutrition in elderly subjects is associated with increased risk of falls, disability, overall morbidity and mortality, health-related costs, and decreased quality of life [ 2 , 12 , 13 , 14 ]. The systematic review and meta-analysis performed by Leij-Halfwerket al [ 14 ] demonstrated that up to 28% of older adults in Europe are at risk of malnutrition, which was assessed with various diagnostic tools.…”
Section: Introductionmentioning
confidence: 99%